1438 Evaluation of the "Freggie Friday" Program to Promote Fruit and Vegetable Consumption in Canadian Elementary School-Aged Children. (October 2012) - Adamo, KB; Colapinto, C; Harvey, A; Grattan, KP; Barrowman, N; Goldfield, GS
Abstract : Background: While Canada is one of the world's most prosperous nations, the health of our children is dismal, with obesity rates amongst the highest in the world. A healthy diet, including at least 5 to 6 daily servings of fruit and vegetables, is of profound importance to child health. Aim: To evaluate the efficacy of a fruit and vegetable program 'Freggie Fridays' developed to encourage Canadian elementary school children (grades 1 to 6) to eat the recommended number of fruit and vegetable servings each day. Methods: A prospective quasi-experimental trial compared schools receiving the "Freggie Friday" curriculum as the intervention (n= 8) to those not receiving the curriculum as control (n=6). The primary outcome measure was the difference in levels of fruit and vegetable consumption as measured by a food frequency questionnaire. Information on attitudes and knowledge of fruit and vegetable consumption was attained using an adapted version of the validated Pro-Children study questionnaire. Results: A total of 807 of the 942 children who completed the baseline questionnaires completed the follow-up questionnaires (450 intervention and 357 control). A mixed effects regression model indicated no significant intervention effects on fruit or vegetable consumption, snack food consumption, or knowledge or attitudes relating to fruit and vegetable consumption. Conclusions: Despite clear messaging and a sound program, it appears that adding a nutritional program, which expects busy teachers to add this to their educational curriculum, may not be the most efficacious method of eliciting healthy dietary behaviour change in Canadian elementary school-aged children.